Supervision By The BPOM Regarding The Circulation Of Illegal Cosmetic Products : The Case Of Reza Gladys - Yuliana Munthe (Law Research Review Quarterly, 2026)
This study aims to analyze the effectiveness of oversight conducted by the Indonesian Food and Drug Administration (BPOM) regarding the circulation of illegal cosmetic products in Indonesia through a case study of products marketed by Reza Gladys. The rampant distribution of illegal cosmetics, particularly through digital platforms and social media, highlights structural challenges in ensuring business operators’ compliance with product safety, quality, and legality standards as stipulated in laws and regulations. This study employs a normative legal methodology with a legislative and conceptual approach to examine legal provisions regarding BPOM’s pre-market and post-market oversight mechanisms, as well as business operators’ obligations to obtain marketing authorization before products are distributed. The results of the study indicate that the circulation of illegal cosmetics without marketing authorization poses significant risks to consumers because they do not undergo a safety evaluation process and do not provide accurate information regarding composition or usage instructions. A case study of products marketed by Reza Gladys revealed violations including the absence of marketing authorization, misclassification of cosmetics, and the use of marketing methods that could potentially mislead consumers. These conditions have resulted in a failure to uphold the principles of legal certainty, consumer protection, and safety standards that the state is obligated to ensure. The findings of this study confirm that although the Indonesian Food and Drug Administration (BPOM) already has a comprehensive regulatory framework, oversight mechanisms still need to be strengthened through the optimization of digital monitoring, enhanced law enforcement capacity, and interagency coordination to minimize loopholes in the circulation of illegal cosmetics. Thus, this study contributes to efforts to strengthen consumer legal protection amid the increasing dynamics of the cosmetics industry.